Implementation of Al-Quran Learning With the Iqra' Method at Bukit Taman State Elementary School Sukamerindu Musi Rawas South Sumatra - Umroni, U; Romelah , R (Suhuf: International Journal of Islamic Studies, 2025)
SDN Bukit Taman Desa Sukamerindu is a Public Elementary School that uses the Iqra method to learn the Quran. Schools use the Iqra' method to help and facilitate learning to read the Quran. The Iqra' method is very popular in Indonesia and is commonly used in public and private elementary schools. This study aims to analyze the implementation of the Iqra' method to improve the ability to read the Quran at SDN Bukit Taman Desa Sukamerindu Musi Rawas. The study results indicate that the Iqra' method has improved students' ability to read the Quran with support from the principal, teacher qualifications, facilities, parental involvement and adaptation of Iqra' materials. The assessment involved various methods, including reading tests, oral assessments, classroom observations, and individual project evaluations, illustrating a significant increase in the ability to read the Quran of students who follow the Iqra' method. This study contributes to understanding how the Iqra' method can be successfully implemented in the national curriculum that positively impacts students' learning of the Quran.